2016
DOI: 10.1186/s12967-016-0918-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the intramyocardial implantation of stromal vascular fraction in patients with chronic ischemic cardiomyopathy

Abstract: BackgroundStromal vascular fraction (SVF) can easily be obtained from a mini-lipoaspirate procedure of fat tissue. The SVF contains a mixture of cells including ADSCs and growth factors and has been depleted of the adipocyte (fat cell) population. We evaluated the safety and efficacy of administering SVF intra-myocardially into patients with chronic ischemic cardiomyopathy.MethodsA total of 28 patients underwent a local tumescent liposuction procedure to remove approximately 60 ml of fat tissue. The fat was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 34 publications
(29 reference statements)
1
46
0
Order By: Relevance
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…These freshly isolated cells obtained from adipose tissue by enzymatic or non-enzymatic dissociation are also termed stroma vascular fraction (SVF) and comprise a heterogeneous mixture containing ASCs, endothelial (progenitor) cells, blood cells, pericytes and other cell types [166]. Since then, other phase I and II clinical studies confirmed the safety and usability of these cells [167][168][169]. However, the two largest placebo-controlled clinical trials, including 27 and 31 patients respectively, failed to detect significant changes in LV functions or volumes after the transplantation of adipose-derived cells, although an improvement in maximal oxygen consumption was observed [167,168].…”
Section: Adipose-derived Stem and Progenitor Cellsmentioning
confidence: 99%
“…Fat tissue can be easily and safely harvested and SVF can be collected bedside making it an attractive therapeutic option for physicians to offer to their patients [19]. A variety of publications have reported on the injection of SVF including: osteoarthritis [20, -21], degenerative disc disease [22], sclerosis [23], tendinopathy [24], congestive heart failure [25], chronic obstructive pulmonary disease (COPD) [26], radiation necrosis [27], xerostomia [28], psoriasis [29], and multiple sclerosis [30].…”
Section: Introductionmentioning
confidence: 99%